The Effect of Firm Growth on Firm Value: Profitability as Mediation and Dividend Policy as Moderation - Ramadhina, Ghaitsa Maghfira; Sanusi, Fauji; Khaerunnisa, Enis (Management Science Research Journal, 2025)
This study aimed to examine how the effect of company growth on firm value, by considering the role of profitability as a mediating variable and dividend policy as a moderating variable. The object of research is focused on companies in the industrial sector listed on the Indonesia Stock Exchange during the period 2018 to 2023. The approach used is quantitative, by exploring the causal relationship comparatively. The data analyzed is secondary data taken from the financial statements of each company, either through the official website of the Indonesia Stock Exchange (IDX) or from the official website of the relevant company. The research sample was determined by purposive sampling method in industrial companies listed on the IDX during 2017 to 2022. The type of data used is panel data, which is analyzed using SPSS and Hayes Process software. The analysis stages start from descriptive statistics to conditional process analysis. The results of hypothesis testing show that: 1) Company growth has a negative and insignificant effect on firm value. 2) Company growth has a positive and significant effect on profitability. 3) Profitability has a positive and significant effect on firm value. 4) Profitability is able to mediate the effect of asset growth on firm value. 5) Dividend policy is not able to moderate the effect of asset growth on firm value.